Children and their brands: how young consumers relate to brands. Issue 2 (19th March 2018) - Lopez, Alberto; Rodriguez, Rachel
Abstract : Purpose: The purpose of this study is to understand and explain the process by which child consumers form relationships with brands. Specifically, the authors attempt to understand how child consumers conceptualize brands, why and how they decide to engage in relationships with brands and why they decide to breakup with brands though sometimes reconcile with them. Design/methodology/approach: A mixed methodology was followed in this research. On the basis of an ethnographic approach, ten in-depth interviews were conducted among 8-12-year-old girls. Subsequently, a survey was completed by 122 children (boys and girls) to quantitatively examine the hypotheses formulated after the qualitative phase. Findings: Findings from both the qualitative and quantitative studies highlight and confirm that children conceptualize brands according to visual branding components, signs and promotional activities. Furthermore, children make moral evaluations of brand behaviors and judge them as "good" or "bad". More importantly, the authors propose two typologies: one for the reasons children decide to engage in a positive relationship and another for why children engage in a negative relationship with a brand. Additionally, the authors found that children report having an active or passive relationship role according to the characteristics of the brand relationship. Moreover, despite their young age, children report having broken up relationships with several brands; the reasons are categorized into positive and negative breakups. Finally, the authors found that positive breakups lead to more probable brand relationship reconciliation than negative breakups. Originality/value: Despite a vast body of literature in the child consumer behavior field, there is scarce research regarding brand relationship phenomena. To the best of the authors' knowledge, this is the first empirical research conducted with child consumers, addressing brand relationship formation, dissolution and reconciliation.